Human chorionic gonadotropin (hCG) plasma levels at oocyte retrieval and IVF outcomes - Matorras, R. (Springer US, 2012)
PURPOSE: The aim of our study was to ascertain the influence of hCG levels at oocyte pick-up on IVF outcomes, and their relationship with clinical parameters. METHODS: A prospective study was performed including 473 women undergoing IVF, aged under 40 years. Blood samples to analyze hCG levels were obtained at the time of follicular aspiration, 36 h after the administration of 250 μg of recombinant hCG. RESULTS: Neither the numbers of oocytes obtained or fertilized, nor the pregnancy rate, were correlated with hCG levels. Moreover, hCG values were very similar in women who did and did not become pregnant (123.3 ± 48.7 and 117.5 ± 44.7 mUI/mL). Cases in which no oocytes were recovered after follicular aspiration had similar hCG levels to those in which more than 1 oocyte was obtained. On the other hand, hCG levels were negatively related to body mass index, weight, and age. CONCLUSIONS: These data indicate that after the administration of 250 μg of recombinant hCG, hCG levels are not responsible for failure to recover oocytes. Specifically, there was no correlation between plasma hCG levels and the number of oocytes obtained or other markers of IVF outcome. There was, however, an inverse relationship with BMI, body weight and age.